2019
DOI: 10.1363/psrh.12103
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Systematic Review of Women's Experiences Using Contraceptive Vaginal Rings: Implications for New Technologies

Abstract: CONTEXT Vaginal rings are available for contraception and hormone replacement, and are being developed as HIV/STD or multipurpose prevention technologies. A comprehensive understanding of women's expectations of and experiences with rings is urgently needed to inform product development and to optimize ring use. METHODS Three databases (PubMed, Global Health and CINAHL) were searched for English‐language, peer‐reviewed articles published between January 1996 and November 2017 that reported qualitative data on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 74 publications
1
16
0
1
Order By: Relevance
“…Perception of the ring of user was sparsely documented and data on ring expulsions were limited in the identified studies. However, when documented, ring-related reasons (slippage, expulsion, vaginal problems, or discomfort) contributed for a proportion of women to discontinuation of all the types of CVRs and confirmed findings from previous studies ( 55 , 59 ). Expulsions and mechanical properties of the ring were included as a specific dimension in acceptability theoretical frameworks that were used in 2 included studies ( 26 , 27 ) and in vaginal ring HIV prevention studies ( 8 ) and deserve to be further addressed in future studies.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Perception of the ring of user was sparsely documented and data on ring expulsions were limited in the identified studies. However, when documented, ring-related reasons (slippage, expulsion, vaginal problems, or discomfort) contributed for a proportion of women to discontinuation of all the types of CVRs and confirmed findings from previous studies ( 55 , 59 ). Expulsions and mechanical properties of the ring were included as a specific dimension in acceptability theoretical frameworks that were used in 2 included studies ( 26 , 27 ) and in vaginal ring HIV prevention studies ( 8 ) and deserve to be further addressed in future studies.…”
Section: Discussionsupporting
confidence: 88%
“…Ease of insertion/removal/reinsertion of CVRs was reported in most included studies and rated high including in Latin American or African settings. Among the included studies, qualitative data on actual experiences of women while using the ring showed that initial worries related to CVR itself or its use, such as aspect, insertion, removal, and feeling the ring inside the vagina, improved over time ( 26 , 30 , 52 ), as it is also reported in 1 qualitative systematic review of CVR and 1 systematic review of vaginal rings ( 55 , 56 ). Initial concerns sometimes required additional support from the provider or practice from the user ( 30 , 55 ) or benefited of an adjustment period as reported among adolescents and younger users in the US ( 52 ).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations